New hole transport styrene polymers bearing highly π-extended conjugated side-chain moieties for high-performance solution-processable thermally activated delayed fluorescence OLEDs. Issue 11 (2nd March 2021) - Lee, Ji Hye; Hwang, Jinhyo; Kim, Chai Won; Harit, Amit Kumar; Woo, Han Young; Kim, Hyung Jong; Kim, Yong Woo; Choi, Dae Hyuk; Cho, Min Ju; Choi, Dong Hoon
Abstract : New polystyrene-based polymers with high π-extended hole transport pendants were synthesized to obtain a low turn-on voltage and high efficiency in solution-processed green TADF-OLEDs. Abstract : Two new hole transport styrene polymers, 2DMFCz and 2DBFCz, were successfully synthesized via radical polymerization. The design concept aims to investigate the hole-transporting ability and energy-level tunability by introducing bis(9, 9-dimethyl-9 H -fluoren-2-yl)aminocarbazole and bis(dibenzo[ b, d ]furan-2-yl)aminocarbazole as side-chain pendants. They were found to show good solubility in chlorobenzene but poor solubility in toluene, similar to poly(9-vinylcarbazole) (PVK). The highest occupied molecular orbital levels of 2DMFCz and 2DBFCz were determined to be −5.23 eV and −5.31 eV, respectively, while hole mobilities were estimated to be 1.65 × 10 −7 cm 2 V −1 s −1 and 1.48 × 10 −8 cm 2 V −1 s −1 measured by the space-charge limited-current method. Subsequently, in solution-processed green thermally activated delayed fluorescence organic light-emitting diodes (TADF-OLEDs), the 2DMFCz - and 2DBFCz -based devices exhibited a relatively low turn-on voltage of 2.7 V and higher maximum external quantum efficiencies of 23.84% and 21.11%, respectively. These values were superior to those of a PVK-based device. The polymer hole-transport materials presented in this study are promising materials that can play a significant role in improving the performance of TADF-OLEDs fabricated through a solution process in the future.